Surgery Under General Anesthesia Alleviated the Hyperactivity but Had No Effect on the Susceptibility to PND in ADHD Rats - Zhang, Peng; Xu, Feifei; Zhao, Guangchao; Zhang, Xinxin; Li, Ao; Dong, Hailong; Xiong, Lize (Frontiers in Psychiatry, 2019)
Background: Attention-deficit hyperactivity disorder (ADHD) is a typical neuropsychiatric disorder characterized by inattention, impulsivity, and hyperactivity, particularly in children. Recent studies demonstrated a close relationship between the development of ADHD and surgery under general anesthesia. However, few studies illustrated if ADHD symptoms changed after surgery. Meanwhile, whether these individuals with natural neural impairment were sensitive to postoperative neurocognitive disorder (PND) still remain unclear. Methods: Spontaneously hypertensive rats (SHR) were utilized as spontaneous ADHD animal model and Wistar-Kyoto (WKY) rats as non-ADHD animal model. We evaluated the variation of neurocognitive function and locomotor activity of the rats undergoing experimental laparotomy with general anesthesia by isoflurane. Neurocognitive function was assessed by fear conditioning test for contextual memory and Morris water maze (MWM) for spatial memory. Depressive-like behavior after surgery was detected by forced swim test, and open-field test and elevated plus maze test were utilized to evaluate locomotor activities and anxiety. Furthermore, we compared electroencephalogram (EEG) signal in ADHD and WKY rats under free-moving conditions. Afterward, c-Fos staining was also utilized to detect the excitatory activity of neurons in these rats to explore the neural mechanism. Results: Locomotor activity of SHR assessed by average speed and number of line crossings in the open-field test decreased 1 week after surgery under general anesthesia, but there was no difference concerning anxiety levels between SHR and WKY rats after surgery. This phenomenon was also paralleled with the change in EEG signal (delta band 0∼3 Hz). Surgery under general anesthesia had no effect on spatial and contextual memory, while it improved spontaneous depression in SHR. The expression of c-Fos was downregulated for at least 1 week in the nucleus accumbens (NAc) area of ADHD rats’ brain after surgery. Conclusion: ADHD rats were not sensitive to PND. Surgery with general anesthesia could partly improve the hyperactivity symptom of ADHD rats. This mechanism was related to the suppression of neural activity in the cerebral NAc of ADHD rats induced by general anesthetics.